A survey on the stage designs of three theaters in U.P Diliman - Ugaban, Vilma U.; Florendo, Raquel Baltazar (1989.)
The study is ab descriptive analysis of the stage design used by three theaters in U.P. Diliman. A background on theater was provided for deeper understanding on the considerations, for stage designing. The factors affecting stage desgn are the script, idea of the director and other limitations. In the case of U.P. theaters stage design is affected by lack of budget. This consequently lead to lack of equipment, materials and personnel. The creation of a set of designing group was the the outcome of these limitations concerning stage design. The Guerrero and Engineering theater are primarily for plays, rarely do they present pure musical shows. The engineering theater is for horror plays and is a venue for poorly produced shows. The priority of the Abelardo is concert, dances or the like. Plays are also presented there occasionally. The Abelardo also held conventions, symposiums, orientation, etc. It is not actually a theater but is an auditorium.
Thesis (BSID)--University of the Philippines Diliman.
Keywords: Theaters -- Philippines -- Quezon City -- Stage setting and scenery